2016
DOI: 10.1039/c6cp01943a
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of imidazolium tricyanomethanide ionic liquids: experiments and molecular simulation

Abstract: The low-viscous tricyanomethanide ([TCM]À )-based ionic liquids (ILs) are gaining increasing interest as attractive fluids for a variety of industrial applications. The thermophysical properties (density, viscosity, surface tension, electrical conductivity and self-diffusion coefficient) of the 1-alkyl-3-methylimidazolium tricyanomethanide [C n mim][TCM] (n = 2, 4 and 6-8) IL series were experimentally measured over the temperature range from 288 to 363 K. Moreover, a classical force field optimized for the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 135 publications
2
34
0
Order By: Relevance
“…In our previous work on thermophysical properties of tricyanomethanide-based ILs it was concluded that ion association in its different forms (e.g. ion-ion correlations and aggregates) could be responsible for the decrease in number of effective charge carriers and hence lower conductivity [11]. The vapor phase non-idealities are modeled using the Redlich-Kwong (RK) EoS.…”
Section: [C 6 Mim][tcm] Absorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work on thermophysical properties of tricyanomethanide-based ILs it was concluded that ion association in its different forms (e.g. ion-ion correlations and aggregates) could be responsible for the decrease in number of effective charge carriers and hence lower conductivity [11]. The vapor phase non-idealities are modeled using the Redlich-Kwong (RK) EoS.…”
Section: [C 6 Mim][tcm] Absorption Processmentioning
confidence: 99%
“…The thermophysical properties of [C 6 mim] [TCM] and the CO 2 solubilities are reported in our previous works. [11,14] The process simulations are solved in the equation-oriented (EO) mode. The EO strategy solves mass and energy balances for the entire flowsheet simultaneously avoiding nested convergence loops and is more effective for processes containing recycle streams and design specifications than the sequential modular mode.…”
Section: Process Simulationmentioning
confidence: 99%
“…Just like for the ILs in the DES, the internal resistance of a fluid at shear stress and intermolecular interactions are the main influence of the viscosity values obtained. DES and Iĺs also share the feature of presenting higher viscosities than other molecular solvents and their differences are associated with hydrogen interactions. …”
Section: Resultsmentioning
confidence: 99%
“…Based on the SHAP value, it is clear that a high value of IPC (denoted by the red color) negatively impacts the output. As the IPC descriptor is related to the content of the molecule, higher values of the feature delineates bulky cations, for example those containing long alkyl chains, slowing down the dynamics of the system 88,89 . Furthermore, Figure S10 (a) also shows the relation between the IPC descriptor of the cation and experimental ionic conductivity at 298.15 K, demonstrating the effect of the descriptor on the ionic conductivity; there is a general trend of decreasing ionic conductivity with IPC as revealed by the SHAP analysis.…”
Section: Model Interpretationmentioning
confidence: 99%